Konsep Being Perspektif Filsafat dan Islam - Suhermanto Jakfar (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2017)
This article discuss the concept of being in the perspective of existentialism and Islam. The closest similarity to the word â€œbeingâ€ is to on (Ancient Greece), as the word of einai, to be (on, onta). For Parmenides, â€œbeingâ€ (to on) is one, eternal and unchanging. Gabriel Marcel calls the way the human being with the term Ãªtre-au-monde, etre in carne, geist-in-welt. Martin Heidegger uses a formula being in the world to characterize human life. Being in the world as a feature of human life, human beings are in the situation. Living in a world of concrete means that there are human relationships with the situation. Sartre said that the real one where there are two, namely: Iâ€™etre en soi and Iâ€™etre pour Soi. For Sartre, Iâ€™etre en soi is the idea that only a concrete phenomenon has ontological status; only something concrete is real. Unlike the being-in-itself, for Sartre the concept of being-for-itself is a state of being that comes with the awareness and self-control. The concept of being (wujÃ»d) by SuhrawardÃ® is a mental concepts (mahfÃ»m) that do not have the type and diferensia. In the illumination philosophy of SuhrawardÃ®, the idea of â€‹â€‹wujÃ»d can not be separated from nature and depiction of light. The philosophy of wujÃ»d by Mulla SadrÃ¢ stands on three basic principles of fundamental importance. These three principles are as follows: wahdat al-wujÃ»d, tashkÃ®k al-wujÃ»d, and tashkÃ®k. While Mohammad Iqbal emphasis on metaphysics and anthropological philosophy. Iqbal gives greater emphasis on more concrete dimensions, namely khudi (ego).